2022
DOI: 10.3389/fnagi.2022.833150
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Grouping During Binocular Rivalry in Mild Glaucoma

Abstract: PurposeThis study tested perceptual grouping during binocular rivalry to probe the strength of neural connectivity of the visual cortex involved in early visual processing in patients with mild glaucoma.MethodsSeventeen patients with mild glaucoma with no significant visual field defects and 14 healthy controls participated. Rivalry stimuli were 1.8°-diameter discs, containing horizontal or vertical sine-wave gratings, viewed dichoptically. To test the grouping, two spatially separated identical stimuli were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 51 publications
(90 reference statements)
1
7
0
Order By: Relevance
“…In line with this, some studies reported abnormalities in perceptual, cognitive functions and sleep quality in glaucoma patients. For example, glaucoma patients were found to have elevated visual crowding effect 34 , impairments on perceptual switch during binocular rivalry [35][36][37] , declines in visual categorization 39,40 , visual attention 41 and cognitive capacity 39,40,42 as well as sleep disturbance 67,68 . Thus, we propose that there could be a functional link between GABA reduction and the reported abnormalities in glaucoma patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this, some studies reported abnormalities in perceptual, cognitive functions and sleep quality in glaucoma patients. For example, glaucoma patients were found to have elevated visual crowding effect 34 , impairments on perceptual switch during binocular rivalry [35][36][37] , declines in visual categorization 39,40 , visual attention 41 and cognitive capacity 39,40,42 as well as sleep disturbance 67,68 . Thus, we propose that there could be a functional link between GABA reduction and the reported abnormalities in glaucoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, glaucoma patients were found to present impairments on some of the perceptual and cognitive functions where GABAergic signals are thought to be involved. These include abnormalities in visual crowding effect 34 , binocular rivalry [35][36][37][38] , visual categorization 39,40 , visual attention 41 , and cognitive capacity 42 .…”
Section: Introductionmentioning
confidence: 99%
“…Psychophysical measures were recorded during rivalry test and consisted of rivalry rate and total time of exclusive percept dominance. The rivalry test setup used was the same as previously reported (Tarita-Nistor et al, 2020 ; Issashar Leibovitzh et al, 2022 ). In summary, the rivalry stimuli were created using a graphics and psychophysics software VPixx (VPixx Technologies, Inc., Montreal, QC) and projected on an iMac computer screen with a resolution of 1,680 × 1,050 pixels.…”
Section: Methodsmentioning
confidence: 99%
“…It is not understood if changes observed throughout the glaucomatous brain manifest in functional changes. Recently, we employed a binocular rivalry paradigm to probe the function of specific brain structures in patients with early glaucoma (Tarita-Nistor et al, 2019 , 2020 ; Issashar Leibovitzh et al, 2022 ). Binocular rivalry occurs when 2 different images are presented separately to each eye at the same retinal location and are viewed dichotically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation